Development of Student Worksheets (LKPD) Multiplications to Overcome Operational Difficulties Calculate Multiplications Story Road - Nasution, Lailam Mahrani; Siregar, Nurdiana (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2024)
The aim of this research is to describe the development stages of the multiplication student worksheet (LKPD) to overcome the difficulties of calculating multiplication operations and to find out whether the multiplication student worksheet (LKPD) can meet the criteria of validity, practicality, and effectiveness. This research uses a type of development research or Research and Development (R&D) and uses the ADDIE development model, which includes Analysis (analyzing), Design (designing), Development (developing), Implementation (applying), and Evaluation (evaluating). Data collection instruments used were material expert validation sheets, media validation sheets, student response questionnaires, and test sheets. The data collection techniques used by researchers in this research were interviews, validation sheets, learning outcomes tests, and student response questionnaires. In this research, the data obtained was analyzed qualitatively and quantitatively. Qualitative analysis is used to describe the product development process. Quantitative analysis is used to describe product quality assessments, response questionnaires, and learning outcomes tests. The results of data analysis are used to improve products. This research was conducted in MIS Madinatussalam. The population in this study were students in class III-6 MIS Madinatussalam, totaling 30 students. Meanwhile, sampling in this research used a total sampling technique or used the entire population as the research sample. Using purposive random sampling, the research subjects were grade III elementary schools. The results of the research showed that the average total validity value obtained from material experts was 92.8% and media experts were 86.6%, which means that the LKPD for the multiplication of stacked roads that was developed had met the valid criteria. The results of the analysis of the practicality of the LKPD learning media for multiplication of stacked paths show that the average total practicality value of student responses is 88.21%, which is in the value range (81% - 100%). In the trial test of learning outcomes on effectiveness, an average N-gain value of 0.44 was obtained and met the range 0.3 ≤ n-gain ≤ 0.7.